Building national security through human security: Seasonal migration from Upper Mustang - Khattri, Man Bahadur (Unity Journal, 2020)
Migration is one of the essential social-cultural phenomena of human being around the world. Seasonal migration is one of the human security dimensions directly related to the national security of a country. This paper explores the human security dimension closely related to seasonal migration and national security which has reasons, processes, and destinations of the Lobas of Upper Mustang, Nepal. The survey, interview, and field observation (Upper Mustang, Western Hills of Nepal and Vanarashi, India) were the principal methods of data collection. The findings of the research are that both married males and females having agriculture and livestock occupations of the large family go for seasonal migration from Upper Mustang, Nepal. The dominant age group of migrants is 20-50 years. The level of literacy, language efficiency, and social network plays a determining role in choosing the destination and period of stay out. They usually migrate to a group and use multiple modes of transportation for their travel. For business, they use the social network. They rent a room to live in. For business investment, they use mostly their own money and some they borrow from moneylenders. They not only work themselves also employ Nepali speaking youths in Vanarashi. Their property in Upper Mustang is taken care of mostly by their family members. They bring cash and kind as their earning while returning home.